Strategi Pengelolaan Konten Media Sosial BPBD Kabupaten Subang untuk Edukasi dan Mitigasi Bencana - Muhammad Adzki Haidar Hutfhi; Fitria Zulfa; Yuliana Yuliana; Aminudin Aminudin (PT Barkah Ilmi Fiddunya, 2026)
. This research aims to analyze the implementation of SIM and BPBD Subang Regency's social media content management strategy in the context of education and disaster mitigation, as well as identifying the technical and non-technical obstacles faced. Using qualitative methods through interviews, observations and documentation studies, this research found that the Subang Regency BPBD has implemented a strict report verification mechanism to prevent hoaxes and ensure the accuracy of information before it is followed up by the BPBD team. Social media, especially Instagram, is used as the main channel for disseminating emergency information, public education and cross-sector coordination, although the quality and consistency of educational content still needs to be improved. Findings also show that the greatest resistance lies in two-way communication with the Community, especially the inconsistency of reporters in providing additional information which hampers field responses. Overall, the implementation of SIM for the use of social media by BPBD Subang Regency is considered quite effective, but still requires strengthening the aspects of disaster literacy, optimizing digital features, increasing the capacity of media managers, and collaborative integration between agencies to strengthen preparedness and reduce disaster risk in Subang Regency.